EVALUASI KEBIJAKAN BANTUAN KEUANGAN PARTAI POLITIK : (Studi tentang Peraturan Walikota Denpasar No. 60 Tahun 2019) - I Nyoman Adi Surya Sukandia (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
As an organization that is obliged to realize the ideals of the Indonesian nation, welfare for the people ofIndonesia, protect and maintain the integrity of the Unitary State of the Republic of Indonesia and develop democraticlife, political parties certainly need financial support from the government to carry out activities that canfulfill their responsibilities, such as carrying out political education activities for cadres, sympathizers and thecommunity. As stated in Perwali Denpasar City No. 60 of 2019. identification of research problems: the lack of clarity in the formulation in determining the amount of assistance received by each political party and the absence of benefits felt by the community from political parties. This study uses the evaluation theory of Karl Luwig von Bertaalanffy focusing on three indicators: input evaluation, process evaluation, and influence evaluation. Data analysis techniques use the Miles and Huberman analysis model. The research findings are that there are still many political parties that do not understand the formula for calculating the amount of assistance received, the lack of public political education and has not had a significant influence on people's understanding of healthy politics in building political ethics and culture.